Study protocol for a single-blind, randomised controlled, non-inferiority trial of internet-based versus face-to-face cognitive behaviour therapy for obsessive–compulsive disorder. Issue 9 (5th September 2018) - Rück, Christian; Lundström, Lina; Flygare, Oskar; Enander, Jesper; Bottai, Matteo; Mataix-Cols, David; Andersson, Erik
Abstract : Introduction: Expert guidelines recommend cognitive–behavioural therapy (CBT) as a first-line treatment for obsessive–compulsive disorder (OCD), but the majority of patients with OCD do not have access to CBT. Internet-delivered CBT (ICBT) has the potential to make this evidence-based treatment more accessible while requiring less therapist time than traditional face-to-face (f2f) CBT. Data from six clinical trials suggest that ICBT for OCD is both efficacious and cost-effective, but whether ICBT is non-inferior to traditional f2f CBT for OCD is yet unknown. Methods and analysis: A single-blind, randomised, controlled, non-inferiority trial comparing therapist-guided ICBT, unguided ICBT and individual (f2f) CBT for adult OCD patients. The primary objective is to investigate whether ICBT is non-inferior to gold standard f2f CBT. Secondary objectives are to investigate if ICBT is equally effective when delivered unguided, to establish the cost-effectiveness of ICBT and to investigate if the treatment outcome differs between self-referred and clinically referred patients. Participants will be recruited at two specialist OCD clinics in Stockholm and also through online self-referral. Participants will be randomised to one of three treatment conditions: F2f CBT, ICBT with therapist support or unguided ICBT. The total number of participants will be 120, and masked assessments will be administered at baseline, biweekly during treatment, at post-treatment and at 3-month and 12-month follow-ups. The main outcome measure is the clinician-rated Yale-Brown Obsessive Compulsive Scale (Y-BOCS) at 3-month follow-up. The margin of non-inferiority is set to 3 points on the Y-BOCS using a 90% CI. Ethics and dissemination: The study has been approved by the Regional Ethics Board of Stockholm (REPN 2015/1099-31/2) and registered at Clinicaltrials.gov (NCT02541968 ). The study will be reported in accordance with the Consolidated Standards of Reporting Trials statement for non-pharmacological trials. The results will be published in peer-reviewed academic journals and disseminated to patient organisations and media. Trial registration number: NCT02541968 ; Pre-results.